2015
DOI: 10.5206/cjsotl-rcacea.2015.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Fail in a Final Pre-service Teaching Practicum

Abstract: This article presents a Canadian perspective on the issue of failure to fail in Bachelor of Education programs. The issue of failure to fail in Bachelor of Education programs is one that had not been explored in any great detail. What literature does exist focuses on the strain that a teacher experiences when s/he mentors a student teacher (Siebert, Clark, Kilbridge, & Peterson, 2006) and the wide variety of situations that can result in failure (Sudzina & Knowles, 1992). This study examines whether th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As a result, properly overseeing the work of the remaining students in the group can become difficult for the PPIs. Previous studies involving the experiences of nursing preceptors and other practice educators revealed that overseeing the work of one struggling student is stressful and time-consuming (Cleland et al, 2008;Danyluk et al, 2015;Finch & Poletti, 2014;Jervis & Tilki, 2011). Therefore, this finding is not surprising given that time constraints can leave educators feeling guilty and even resentful toward the failing student for preventing them from fulfilling their obligations to oversee the work of other group members.…”
Section: Emotionally-draining Experiencementioning
confidence: 92%
See 2 more Smart Citations
“…As a result, properly overseeing the work of the remaining students in the group can become difficult for the PPIs. Previous studies involving the experiences of nursing preceptors and other practice educators revealed that overseeing the work of one struggling student is stressful and time-consuming (Cleland et al, 2008;Danyluk et al, 2015;Finch & Poletti, 2014;Jervis & Tilki, 2011). Therefore, this finding is not surprising given that time constraints can leave educators feeling guilty and even resentful toward the failing student for preventing them from fulfilling their obligations to oversee the work of other group members.…”
Section: Emotionally-draining Experiencementioning
confidence: 92%
“…Appendix C contains the critical appraisal of relevant studies reviewed in this chapter. The studies that met the inclusion criteria for the literature review were predominantly qualitative in nature (except for Brown et al, 2012) and originated in the UK (Black et al, 2014;Cleland et al, 2008;Duffy, 2003;Finch & Poletti, 2014;Jervis & Tilki, 2011;Lankshear, 1990), Australia and New Zealand (Duke, 1996;Hawe, 2003;Stokes, 2007), South Eastern Europe (Finch & Poletti, 2014), United States (Amicucci, 2012;DeBrew & Lewallen, 2014;Poorman & Mastorovich, 2014;Fontana, 2009), and Canada (Danyluk et al, 2015;Diekelman & McGregor, 2003;Dudek, 2005;Larocque & Luhanga, 2013;Luhanga et al, 2008a). The CASP for qualitative studies has 10 questions and I assigned one mark to each question for a total score of 10; questions include: "Was there a clear statement of the aims of the research?"…”
Section: Appraisal Of Study Rigourmentioning
confidence: 99%
See 1 more Smart Citation
“…In their article, Danyluk et al (2015) conclude, just like we do, that failure in teacher programme placement studies is never an easy or one-sided matter. It involves teacher education, student, supervisors in schools and the establishment that has received the student.…”
Section: "Separating the Wheat From The Chaff" -Possibilities And Impmentioning
confidence: 99%
“…There has been little discussion on preservice teachers particularly on their CA profile. The existing literature with regards to pre-service teachers focused on the impact of their failure in teaching practicum towards teacher associates, faculty members, and the quality of professional program in general [26]. In addition, similar literature investigated the profile of in-service teachers in Nigeria and claimed that age and gender proved to be non-determinant factors towards their CA [3].…”
Section: Beyond Student's Perspectivementioning
confidence: 99%